Implementation of KYC Principles for Indonesian Payment Services Provider - Wongkar, Kanon Mommsen (Journal of Accounting, Business and Management (JABM), 2024)
Payment Services Providing is a bright yet simple business to run for it requires a merely reliable system to execute transactions among banks as well as other entities. Nevertheless, these services are also utilized by criminals such as terrorists and/or money launderers. This paper is aimed to discuss the complex yet necessary execution of Know Your Customers Principle for a PSP. This is a library research to collect and analyze secondary data covering law and business literature published within 5 years as well as any legislation concerning PSPs. The research concluded that KYC Principles are mandatory for PSP with activities to manage funds such as in the form of e-wallet. Secondly, KYC Principles are not mandatory for PSPs with only activities as payment aggregator, billing provider and/or remittance services provider. At this point, it is suggested firstly to complete the regulations concerning KYC Principles for Indonesian PSPs. Secondly, utilization of KYC Services requires advanced technology concerning the way to obtain customers data as well as its storage and access availability.